10 Rules for Scalable Performance in 'Simple Operation' Datastores. - STONEBRAKER, MICHAEL; CATTELL, RICK (Communications of the ACM, 2011)
The article presents a set of guidelines on scalable SQL and NoSQL datastores which involve relational database management systems (RDBMSs) using multiple servers. It is argued that applications must be designed for scalability in a web 2.0 context, and topics such as operations that span partitions, parallelism, and requirements for consistency guarantees are discussed. Rules are promulgated regarding issues such as high-level languages, automatic recovery, the hazards of multi-node operations, and the advantages of open source software.